The Relationship between Environmental Sanitation and Stunting Incidence in Toddlers Aged 24-55 Months in Desa Penyaring, Sumbawa Regency - Adina Putri, Desy Fadilah; Afriani, Ayu (STIKES Yarsi Mataram, 2021)
Stunting is a health problem because it is associated with the risk of morbidity and mortality, suboptimal brain development, and inhibited motor development and mental growth. Stunting in Sumbawa increased in 2017, decreased by 10.35% in 2018. One of the villages with a high stunting rate in North Moyo District is Penyaring Village, namely 53 children out of 229 children. The purpose of this study was to analyze the various factors that influence the high rate of stunting. In children aged 24-55 months in Penyaring Village. This research is survey research that is observational with a cross-sectional approach. This study population was all houses that had children under five and had diarrhea as many as 34 children under five. The research sample is the entire population. The sampling technique used in this study was using total sampling. Data analysis using the statistical chi-square test (χ2). Based on statistical results using the chi-square test with Asymp.sig results (0.000; p <0.05), which means that environmental sanitation has a significant relationship with the high incidence of stunting. It shows that environmental sanitation is an indirect factor that causes stunting. After all, poor sanitation will increase the incidence of illness, resulting in diarrhea incidence. For this reason, it is hoped that all related parties, especially family or the role of mothers, are important for reducing the incidence of stunting.